2020
DOI: 10.3390/ijerph17207606
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Range of Movement of the Lower Limb in Sport: Advantages of the ROM-SPORT I Battery

Abstract: Range of movement (ROM) assessment is an important strategy to increase physical-technical performance and minimize the risk of sports-related injuries. Currently, there is no consensus regarding which ROM assessment method is the most appropriate. The main objective of this study was to perform a systematic review of the test batteries available for the assessment of lower limb ROM; additionally, we compare the ROM-SPORT I battery with those previously reported in the literature. The systematic review was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 84 publications
1
31
0
5
Order By: Relevance
“…The findings of this study indicate that the average values of the nine ROMs assessed in the futsal players may be categorized as normal or non-limited according to the cutoff scores described in the literature to identify athletes at high risk of sustaining a soft-tissue injury. Similar results were found by Cejudo et al (2014), who after having carried out the same ROM maneuvers and testing procedures [ROM-Sport protocol (Cejudo et al, 2020)] in male futsal players, found hip, knee and ankle ROM average values that may be categorized as normal. From this standpoint, no specific adaptations in the lower extremities joints ROM would be expected as a consequence of futsal training and match play at elite levels.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The findings of this study indicate that the average values of the nine ROMs assessed in the futsal players may be categorized as normal or non-limited according to the cutoff scores described in the literature to identify athletes at high risk of sustaining a soft-tissue injury. Similar results were found by Cejudo et al (2014), who after having carried out the same ROM maneuvers and testing procedures [ROM-Sport protocol (Cejudo et al, 2020)] in male futsal players, found hip, knee and ankle ROM average values that may be categorized as normal. From this standpoint, no specific adaptations in the lower extremities joints ROM would be expected as a consequence of futsal training and match play at elite levels.…”
Section: Discussionsupporting
confidence: 86%
“…The passive hip flexion with knee flexed (HF KF ) and extended (HF KE ), extension (HE), abduction (HA), external (HER) and internal (HIR) rotation; knee flexion (KF); and ankle dorsiflexion with knee flexed (ADF KF ) and extended (ADF KE ) ROMs of the dominant and non-dominant limbs were assessed following the methodology previously described ( Cejudo et al, 2020 ). Briefly, an ISOMED inclinometer (Portland, Oregon) with a telescopic arm was used as the key measure for all tests.…”
Section: Methodsmentioning
confidence: 99%
“…Maximum passive hip flexion with the knee extended range of motion (HF-KE) for HE was performed using the ROM-SPORT battery methodology according to Cejudo et al [67]. Both the non-dominant and dominant lower extremities were evaluated.…”
Section: Assessment Of Hamstring Extensibilitymentioning
confidence: 99%
“…This is of importance, since the most common acute injury in volleyball is located mostly in the ankle, namely the ankle sprain [ 18 ] and it is the most frequent time loss injury in youth female volleyball players [ 19 ]. The importance of flexibility, namely the ability of tissues to achieve the maximum range of movement that is quantitatively measured as joint range of motion (ROM) [ 20 ], for injury avoidance and sport-specific performance is well documented [ 21 ]. The ankle ROM depends on the ankle dorsiflexion and plantar flexion ability and is evaluated in the sagittal plane, with the knee joint angular position at neutral, in 90° flexion or at maximum knee flexion when the examined person is standing or at the supine position [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of flexibility, namely the ability of tissues to achieve the maximum range of movement that is quantitatively measured as joint range of motion (ROM) [ 20 ], for injury avoidance and sport-specific performance is well documented [ 21 ]. The ankle ROM depends on the ankle dorsiflexion and plantar flexion ability and is evaluated in the sagittal plane, with the knee joint angular position at neutral, in 90° flexion or at maximum knee flexion when the examined person is standing or at the supine position [ 20 ]. The range of motion is also measured actively (with muscular contraction only) or passively (movement of the joint caused by external force) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%